Utricularia geminiscapa Benj. (Lentibulariaceae): A new angiospermic record for Bangladesh - Alfasane, Md Almujaddade; Bhuiyan, Rauf Ahmed; Eusufzai, Moniruzzaman Khan (Bangladesh Journal of Plant Taxonomy, 2020)
Abstract not available Bangladesh J. Plant Taxon. 27(1): 191-194, 2020 (June)